On a Subclass of Meromorphic Univalent Functions With Fixed Second Coefficientsassociated with q-Differed Operator - Mahmood, Zena Hameed; Jassim, Kassim Abdulhameed (Iraqi Journal of Science, 2023)
The main object of this article is to study and introduce a subclass of meromorphic univalent functions with fixed second positive defined by q-differed operator. Coefficient bounds, distortion and Growth theorems, and various are the obtained results.